PENGARUH PEMBERDAYAAN TERHADAP KELELAHAN KERJA DAN KECERDASAN EMOSIONAL PERAWAT DAN BIDAN PADA RUMAH SAKIT RUJUKAN DI SULAWESI SELATAN - Roslina Alam (EKUITAS (Jurnal Ekonomi dan Keuangan), 2010)
Nurses and midwives is a profession which serves human beings and humanity, in the sense that the profession of nurses and midwives will give priority to the health of individuals, family and society above their own interest. The services provided by nurses and midwives is based on their knowledge and know-how in nursing which integrates the attitude, intellectual capacity and technical skills of the nurses and midwives based on their willingness and competence in helping others in health and sickness. This research is conducted on nurses and midwives in regional referral hospitals in South Sulawesi, which is comprised of seven hospitals in the municipality of Palopo, regency of Bone, regency of Bulukumba, municipality of Parepare and three other hospitals in the municipality of Makassar. The focus of this research is on the empowerment felt by nurses and midwives in relation to role ambiguity and conflict, job burnout and emotional intelligence. Sample was taken using proportional area random sampling where each unit is determined as much as 10 percent by Gay (in Umar, 2004:108). Sample size is about 200 people. The design of this research is explanatory, which tries to explain the relation among variables through confirmatory analysis and proposition testing. The result of the research shows that: (1) the empowerment has positive and significant impact on role ambiguity and conflict, due to the high expectation and lack of workers in the hospitals, (2) role ambiguity and conflict has positive and significant impact on job burnout, (3) empowerment has insignificant impact on job burnout, (4) job burnout has insignificant impact on emotional intelligence, and (5) empowerment has significant and positive impact on emotional intelligence. This research found that task and responsibility should be adapted to job description and further research should develop other variables in the hospital, improve the autonomy and independence of the nurses and midwives so as to reduce role ambiguity and conflict.